Energy Resilience: Definition and Assessment - Fellipe, Sartori da Silva [UNESP]; Matelli, José Alexandre [UNESP] (Springer Nature, 2024)
The concept of resilience is widely addressed within several areas, including energy one. As a recently introduced idea in the latter, its definition and analysis still varies between approaches. The aim of this chapter is to cover some of the descriptions found in literature, expliciting their common points and then converging to a single definition. Initially, this concept will be explored in the context of several systems, then advancing to engineering systems and finally to energy ones, including both generation and transmission systems. In addition, several researches addressing energy resilience will be selected and detailed, in a way to point out some analysis patterns, focusing on two types of factors influencing the resilience assessments: the ones inboard and those abroad the system. For each type, some of the important methods will be highlighted. The important founds of the survey will be discussed and summarized, as a way to outline the context of resilience within the energy field and emphasize the most recent advances, guiding the future research.
Keywords: Energy resilience assessment; Energy resilience definition; Energy systems resilience; Engineering systems resilience